Performance of the Ethiopian Somali Goat during different watering Regimes - Mengistu, U. (Swedish University of Agricultural Sciences, 2007)
Water is scarce in the semi-arid regions of Ethiopian and therefore goats are watered intermittently. This can result in dehydration and decreased animal performance. The aims of these studies were to investigate the mechanisms employed by the Ethiopian Somali goat to endure water scarcity and to generate information on milk yield and kid growth. All studies were conducted at the Errer valley research station, eastern Ethiopia. The first study evaluated the effects of watering male goats once daily and every 2nd, 3rd and 4th day for 72 days at indoor conditions. The goats were fed hay ad libitum and were given 200g of concentrates daily. In the second study, 14 does and their kids were studied 3 to 4 months after parturition in the hot dry season. They were randomly distributed to once daily or once every 4th day watering. The kids followed the does out on pasture. Every evening, the does were each given 300g concentrates. The kids were offered 100g of concentrate per head and day in group. The third experiment evaluated drinking pattern and milk production of the 12 goats during a rainy period. The does were randomly assigned to two feeding treatments starting 11 to 17 days after parturition and continuing for 72 days. Six goats were each given 250g concentrates every evening and six goats were only grazing. The kids suckled morning and evening. One udder half was hand milked in the mornings. Plasma osmolaity and vasopressin concentration increased to gigs levels on the 4th day of water deprivation in the males and initially in late lactating does. It shows that four days of water deprivation challenged water balance. The osmolality in every 4th day watered does increased less as the cycles continued, indicating that the goats economized on water. Intermittently watered does and kids spent more time in the shade and browsed watery plants. Rectal temperature increased daily by about 3.5°C in all does and by 2.5°C and 3.2°C in kids watered daily and every 4th day, respectively, during the hot dry period. Milk yield was about 22% lower than in the group given water daily, kids watered once every 4th day did not gain body weight as fast as those watered daily. Goats did not always drink when offered water during a rainy period. The milk yield was less than half a liter per day although good forage was available. Concentrate supplementation increased milk yield by 13%, but reduced fat percentage. Both does and kids increased their body weight during the rainy period. In conclusion, the Ethiopian Somali goat rapidly adjusts to water shortage and starts to economize on water when subjected to a prolonged period of intermittent waterig. It is important that this unique adaptability is considered in breeding programs aimed at increasing the comparatively moderate milk production. Nevertheless, more than three days interval between watering during the hot dry season is not recommended since it may jeopardize animal performance and welfare.